2007
DOI: 10.1111/j.1471-4159.2007.04920.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of lysosomal acid phosphatase in CLN3‐defective cells and mouse brain tissue

Abstract: Juvenile neuronal ceroid lipofuscinosis (Batten disease) is a neurodegenerative disorder caused by defective function of the lysosomal membrane glycoprotein CLN3. The activity of the lysosomal acid phosphatase (LAP/ACP2) was found to be significantly increased in the cerebellum and brain stem of Cln3-targeted mice during the early stages of postnatal life. Histochemical localization studies revealed an increased LAP/ ACP2 staining intensity in neurons of the cerebral cortex of 48-week-old Cln3-targeted mice as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 59 publications
(129 reference statements)
0
21
0
Order By: Relevance
“…A thorough study of the lysosome proteome has not been performed in cells completely lacking CLN3 function. However, in JNCL cells, or in cells in which CLN3 function is substantially or partially reduced, alterations in trafficking or processing of specific lysosomal enzymes have been reported (Fossale et al, 2004;Junaid and Pullarkat, 1999;Metcalfe et al, 2008;Pohl et al, 2007;Sleat et al, 1998), and lysosomal homeostasis is affected (Holopainen et al, 2001;Kitzmüller et al, 2008;Ramirez-Montealegre and Pearce, 2005). In one instance, exit of a reporter version of the cation-independent M6PR from the TGN was significantly reduced when CLN3 was depleted (Metcalfe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A thorough study of the lysosome proteome has not been performed in cells completely lacking CLN3 function. However, in JNCL cells, or in cells in which CLN3 function is substantially or partially reduced, alterations in trafficking or processing of specific lysosomal enzymes have been reported (Fossale et al, 2004;Junaid and Pullarkat, 1999;Metcalfe et al, 2008;Pohl et al, 2007;Sleat et al, 1998), and lysosomal homeostasis is affected (Holopainen et al, 2001;Kitzmüller et al, 2008;Ramirez-Montealegre and Pearce, 2005). In one instance, exit of a reporter version of the cation-independent M6PR from the TGN was significantly reduced when CLN3 was depleted (Metcalfe et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that ACP2 encoding the lysosomal acid phosphatase was significantly upregulated at the mRNA and protein level in CLN3-deficient mouse brain and patient fibroblasts (9). The basal mRNA expression of ACP2 in lymphocytes, however, appears to be too low to allow detection of alterations between CLN3 patients and controls.…”
Section: Identification Of a Potential New Biomarker For Cln3 Diseasementioning
confidence: 99%
“…Quantitative real-time PCR was performed using TaqMan gene expression assays (Applied Biosystems, Darmstadt, Germany) including predesigned probes and primers sets for mouse cathepsin D (Mm00515587_m1), cathepsin Z (Mm00517687_m1), and bactin (Mm00607939_s1). Quantitative real-time PCR was performed as described previously 44 using the Mx3000P QPCR system (Agilent Technologies, Santa Clara, CA, USA). Expression levels of the analyzed mRNAs were normalized to the amount of b-actin mRNA in the same cDNAs using the comparative CT method (2 -DDCT ).…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%